Analisis Yuridis terhadap Penggunaan dan Peredaran Rokok Elektronik di Indonesia: Studi Komparatif dengan Negara Malaysia - Bunda, Ridho Harapan (FOCUS, 2025)
The increasing use of vape e-cigarettes in Indonesia, particularly among adolescents, poses new challenges in terms of public health and legal regulation. They are often perceived as a safer alternative to conventional cigarettes, although their long-term effects are still not fully understood. This study aims to analyse the regulation of the use and circulation of vape in Indonesia, and compare it with the regulation in Malaysia, in order to identify the similarities, differences, and legal implications of these policies on society. The research method used is a normative juridical approach with literature study and comparative legal analysis. The results show that the regulation in Indonesia is still focused on the fiscal aspect through the application of excise tax, while the supervision of product distribution and content is still weak. In contrast, Malaysia applies stricter regulations, including a ban on sales to individuals under the age of 18 and a ban on the use of nicotine liquids since 2015. The conclusion of this study shows that Indonesia needs to improve its regulations by balancing the protection of public health and economic interests, and learn from the best practices implemented in Malaysia. More comprehensive policies and public education are expected to reduce the prevalence of vape use among adolescents and reduce long-term health risks.